Mutations of photosystem II D1 protein that empower efficient phenotypes of Chlamydomonas reinhardtii under extreme environment in space. - Maria Teresa Giardi; Giuseppina Rea; Maya D Lambreva; Amina Antonacci; Sandro Pastorelli; Ivo Bertalan; Udo Johanningmeier; Autar K Mattoo (PLoS ONE, 2013)
Space missions have enabled testing how microorganisms, animals and plants respond to extra-terrestrial, complex and hazardous environment in space. Photosynthetic organisms are thought to be relatively more prone to microgravity, weak magnetic field and cosmic radiation because oxygenic photosynthesis is intimately associated with capture and conversion of light energy into chemical energy, a process that has adapted to relatively less complex and contained environment on Earth. To study the direct effect of the space environment on the fundamental process of photosynthesis, we sent into low Earth orbit space engineered and mutated strains of the unicellular green alga, Chlamydomonas reinhardtii, which has been widely used as a model of photosynthetic organisms. The algal mutants contained specific amino acid substitutions in the functionally important regions of the pivotal Photosystem II (PSII) reaction centre D1 protein near the QB binding pocket and in the environment surrounding Tyr-161 (YZ) electron acceptor of the oxygen-evolving complex. Using real-time measurements of PSII photochemistry, here we show that during the space flight while the control strain and two D1 mutants (A250L and V160A) were inefficient in carrying out PSII activity, two other D1 mutants, I163N and A251C, performed efficient photosynthesis, and actively re-grew upon return to Earth. Mimicking the neutron irradiation component of cosmic rays on Earth yielded similar results. Experiments with I163N and A251C D1 mutants performed on ground showed that they are better able to modulate PSII excitation pressure and have higher capacity to reoxidize the QA (-) state of the primary electron acceptor. These results highlight the contribution of D1 conformation in relation to photosynthesis and oxygen production in space.